Pengaruh Pembiayaan dan Piutang Terhadap Laba Bersih pada Bank Syariah di Indonesia Periode 2015-2020 - Ira Febrianti; Melya Radiatullah (Universitas Batanghari Jambi, 2023)
the objective of this study is to examine the impact of mudharabah, musyarakah, and murabahah financing on net income in islamic commercial banks in Indonesia. The research methodology utilizes the panel regression analysis method with a fixed effect model. The findings of this study indicate that mudharabah, musyarakah, and murabahah financing collectively have a significant effect on net income. Additionally, mudharabah and murabahah financing individually demonstrate a significant influence on net income, while musyarakah financing does not have a significant effect on net income.